2014
DOI: 10.3390/molecules19079187
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Physicochemical Properties of a Virgin Coconut Oil Emulsion and Commercial Food Supplement Emulsions

Abstract: Food manufacturers are interested in developing emulsion-based products into nutritional foods by using beneficial oils, such as fish oil and virgin coconut oil (VCO). In this study, the physicochemical properties of a VCO oil-in-water emulsion was investigated and compared to other commercial oil-in-water emulsion products (C1, C2, C3, and C4). C3 exhibited the smallest droplet size of 3.25 µm. The pH for the emulsion samples ranged from 2.52 to 4.38 and thus were categorised as acidic. In a texture analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…In order to measure the particle size of the P. serotine defatted flour, the methodology of Khor et al [30] was used with some modifications. The flour was measured in a Mastersizer 3000 Hydro LV (Malvern Instruments Ltd., Worcestershire, UK) using the liquid unit.…”
Section: Particle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure the particle size of the P. serotine defatted flour, the methodology of Khor et al [30] was used with some modifications. The flour was measured in a Mastersizer 3000 Hydro LV (Malvern Instruments Ltd., Worcestershire, UK) using the liquid unit.…”
Section: Particle Sizementioning
confidence: 99%
“…Optical properties of the sample were defined as refractive index 1.43 for PsPC and 1.46 for WPC, water as dispersant and an absorption of 0.1. The results were expressed as means ± standard deviation [30].…”
Section: Droplet Size Measurementmentioning
confidence: 99%
“…VCO naturally contains a 3:1 ratio mixture of MCFAs and LCFAs [25] where the saturated MCFAs comprises two-thirds of coconut oil"s fatty acids, the saturated LCFAs are less than one-third, and the unsaturated fatty acids are less than a tenth of its fatty acids [26]. Coconut oil is about 90% saturated fatty acids and is highly saturated oil [27].…”
Section: B Fatty Acids Composition Of Vcomentioning
confidence: 99%
“…Only recently, Odel et al [59] further proved that LA could hinder the maturity of S. aureus, B. cereus, E. coli, and Salmonella thypimurium, but the inhibition was still lower than the Ciprofloxacin, an antibiotic used to treat a number of bacterial infections. Khor et al [25] concluded that the acidic pH nature of VCO between 2.52 and 4.38 may be an important attribute to its microbial inhibitory action. The antibacterial activity of MCFAs has been summarized in Table II.…”
Section: Antibacterial Action Of Coconut Oilmentioning
confidence: 99%
“…Hidrocolloids can act as surface active gums since it has the ability to create film in the oil droplets surrounding, making the coalescence takes slowly and prevent the emulsion to breakdown. In addition, some other hydrocolloids can stabilize the emulsion by increasing the viscosity of the aqueous stage [5] and [6].…”
Section: Introductionmentioning
confidence: 99%